Arthrodesis of the Trapeziometacarpal Joint Using a Chevron Osteotomy and Plate Fixation. (22nd October 2014) - Shyamalan, G.; Jordan, R. W.; Jarvis, A.
Abstract : Introduction . Trapeziometacarpal (TM) osteoarthritis is common. Despite the availability of numerous surgical options, none has been definitively proven to be superior. This study aims to determine the union rate and key strength following arthrodesis using a chevron osteotomy and plate fixation. Methods . 32 consecutive cases of TM joint arthrodesis performed between 2001 and 2006 were retrospectively identified. A chevron osteotomy was used to resect joint surfaces and fixation obtained using an AO mini T-plate. The patients were followed up for a mean of 65 months. Outcomes included visual analogue pain score, patient satisfaction, pinch strength, radiographic union, radiographic signs of scaphotrapezial arthritis, and complications. Results . The 32 cases included 16 females and 8 males with an average age of 56 years. Overall there was a 90% patient satisfaction rate. Average key pinch strength was 8.4 kg and pain score was 2.5. The union rate was 94%, and the two patients with nonunion underwent successful revision surgery. Only one case of radiographic progression of scaphotrapezoid arthritis was identified during followup. Conclusion . TM joint arthrodesis using a chevron osteotomy and plate fixation has high patient satisfaction and low nonunion rates. The authors endorse this technique in the management of TM joint osteoarthritis.